2023
DOI: 10.1186/s40729-023-00476-0
|View full text |Cite
|
Sign up to set email alerts
|

Short implants compared to regular dental implants after bone augmentation in the atrophic posterior mandible: umbrella review and meta-analysis of success outcomes

Gustavo Sáenz-Ravello,
Benjamín Ossandón-Zúñiga,
Vicente Muñoz-Meza
et al.

Abstract: Purpose To assess the body of evidence of short versus regular implants after bone augmentation (BA) in the atrophic posterior mandible in the context of implant treatment success outcomes. Methods Seven databases, two registries, and reference lists were searched for systematic reviews and meta-analysis (SR/MA), randomized controlled trials (RCTs) and longitudinal studies published in English, Spanish or German since 2012. Confidence in the SR/MA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…There are other treatment alternatives available to rehabilitate partially edentulous jaws with, such as standard implants in grafted bone with open or closed sinus elevation with or without regeneration, nerve transposition (mandible), and alveolar distraction osteogenesis. Several studies compared the performance between short implants inserted in residual bone and standard implants inserted in augmented bone with differing results [ 24 , 32 , 33 , 34 , 35 , 36 ]. Terheyden et al [ 24 ] registered no significant difference in implant survival at 8 years of follow-up using short implants (≤7 mm) or standard implants in augmented bone; however, less complications and decreased marginal bone loss occurred in short implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other treatment alternatives available to rehabilitate partially edentulous jaws with, such as standard implants in grafted bone with open or closed sinus elevation with or without regeneration, nerve transposition (mandible), and alveolar distraction osteogenesis. Several studies compared the performance between short implants inserted in residual bone and standard implants inserted in augmented bone with differing results [ 24 , 32 , 33 , 34 , 35 , 36 ]. Terheyden et al [ 24 ] registered no significant difference in implant survival at 8 years of follow-up using short implants (≤7 mm) or standard implants in augmented bone; however, less complications and decreased marginal bone loss occurred in short implants.…”
Section: Discussionmentioning
confidence: 99%
“…Terheyden et al [ 24 ] registered no significant difference in implant survival at 8 years of follow-up using short implants (≤7 mm) or standard implants in augmented bone; however, less complications and decreased marginal bone loss occurred in short implants. Sáenz-Ravello et al [ 36 ] reported a decreased risk of implant failure, marginal bone loss, and biological complications for short implants in residual bone in the posterior mandible. Buser et al [ 32 ] and Hallman et al [ 33 ], in 5-year prospective studies, both registered cumulative survival rates of 86% and 100% for implants placed in augmented bone, and in patients subjected to maxillary sinus floor augmentation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned for patients with OMFFs, we try to avoid further surgical procedures due to a fundamental concern minimizing a patient's exposure to additional morbidities. Short dental implants have the unmistakable advantage of size, which most often precludes the need for augmentation surgeries and their associated morbidity [48,49]. According to Malet, the most important clinical recommendations for placing short implants [50] is to avoid generating heat.…”
Section: Discussionmentioning
confidence: 99%
“…It is also recommended to splint prosthetic restorations of adjacent short implants [ 10 ]. Concerning the type of prosthetic restoration, it has been reported that cemented restorations are associated with increased survival rates and lower MBL values than screwed prostheses [ 73 ].…”
Section: Discussionmentioning
confidence: 99%